Analisis Perbedaan Sebelum Dan Sesudah Dilakukan Merger Dan Akuisisi Terhadap Harga Saham Pada Perusahaan Perbankan Go Public - Umi Fadilah Fatoni (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
The purpose of this study was to determine the effect of mergers and acquisitions on stock prices carried out by publicly traded banking companies in 2015-2021. The research method used includes the type of event study research. Data obtained by conducting secondary data search. The analytical method used is a quantitative method, with the data analysis technique used is the paired sample t-test. The results showed a decrease in the average change in stock prices after the announcement of mergers and acquisitions was made. From these results, it has not shown any positive influence from mergers and acquisitions. It can be seen that between 10 days before and 10 days after the announcement of the merger, the results are 0,0000611 and – 0,00129. By using a significant level of 5%, the t-count value in the merger and acquisition is 0,561<2,110 or by looking at the probability shows that 0,562 > 0,05. Thus, there is no Significant Different between 10 days before and 10 days after the announcement of the merger ang acquisition. Suggestions that can be given are to add a longer period of research so that a larger sample allows for better results and it is necessary to consider other variables that affect stock prices, such as interest rates, inflation rates, and other macro influences, and in the end will affect research results.